CULTIVATION OF EDIBLE AND MEDICINAL MUSHROOMS - Minotto, Elisandra (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Mushrooms generally belong to Basidiomycetes which harbors numerous species with diversity of metabolites of nutraceutical and therapeutic significance. They are famous healthy food because show high rates of nutrients such as proteins, fibers, carbohydrates, minerals, vitamins, and lipids. When compared with other countries, the edible mushrooms cultivation is considered too small in the Brazil. They are important to development of small properties because can be cultivated in agroindustrial residues generating their economic improvement. Thus, the aim of this short course is to give to the event participants general notions regarding the cultivation of edible and medicinal mushrooms. This theoretical and practical short course aimed to develop knowledge based on lectures and laboratory techniques about the selected theme. Contents showed: diversity of mushrooms and their main morphological and physiological characteristics; nutritional and medicinal properties; biotechnological importance of fungi: methods and culture media for isolating of different mushrooms: Agaricus bisporus, Lentinula edodes and Pelurotus spp.; strain selection of the edible mushrooms, making of spawns and their application to natural substrates, and standardization of cultivation conditions to ensure proper mycelial colonization of the substrates to be followed by different. eywords: Basidiomycetes. Agaricus bisporus. Health.